Mitochondria‐specific antioxidant supplementation does not influence endurance exercise training‐induced adaptations in circulating angiogenic cells, skeletal muscle oxidative capacity or maximal oxygen uptake. (18th September 2016) - Shill, Daniel D.; Southern, W. Michael; Willingham, T. Bradley; Lansford, Kasey A.; McCully, Kevin K.; Jenkins, Nathan T.
Abstract : Key points: Reducing excessive oxidative stress, through chronic exercise or antioxidants, can decrease the negative effects induced by excessive amounts of oxidative stress. Transient increases in oxidative stress produced during acute exercise facilitate beneficial vascular training adaptations, but the effects of non‐specific antioxidants on exercise training‐induced vascular adaptations remain elusive. Circulating angiogenic cells (CACs) are an exercise‐inducible subset of white blood cells that maintain vascular integrity. We investigated whether mitochondria‐specific antioxidant (MitoQ) supplementation would affect the response to 3 weeks of endurance exercise training in CACs, muscle mitochondrial capacity and maximal oxygen uptake in young healthy men. We show that endurance exercise training increases multiple CAC types, an adaptation that is not altered by MitoQ supplementation. Additionally, MitoQ does not affect skeletal muscle or whole‐body aerobic adaptations to exercise training. These results indicate that MitoQ supplementation neither enhances nor attenuates endurance training adaptations in young healthy men. Abstract: Antioxidants have been shown to improve endothelial function and cardiovascular outcomes. However, the effects of antioxidants on exercise training‐induced vascular adaptations remain elusive. General acting antioxidants combined with exercise have not impacted circulating angiogenic cells (CACs). We investigated whether mitochondria‐specific antioxidant (MitoQ) supplementation would affect the response to 3 weeks of endurance exercise training on CD3 +, CD3 + /CD31 +, CD14 + /CD31 +, CD31 +, CD34 + /VEGFR2 + and CD62E + peripheral blood mononuclear cells (PBMCs), muscle mitochondrial capacity, and maximal oxygen uptake ( V O 2 max ) in healthy men aged 22.1 ± 0.7 years, with a body mass index of 26.9 ± 0.9 kg m –2, and 24.8 ± 1.3% body fat. Analysis of main effects revealed that training induced 33, 105 and 285% increases in CD14 + /CD31 +, CD62E + and CD34 + /VEGFR2 + CACs, respectively, and reduced CD3 + /CD31 − PBMCs by 14%. There was no effect of MitoQ on CAC levels. Also independent of MitoQ supplementation, exercise training significantly increased quadriceps muscle mitochondrial capacity by 24% and V O 2 max by roughly 7%. In conclusion, endurance exercise training induced increases in multiple CAC types, and this adaptation is not modified by MitoQ supplementation. Furthermore, we demonstrate that a mitochondrial‐targeted antioxidant does not influence skeletal muscle or whole‐body aerobic adaptations to exercise training. Key points: Reducing excessive oxidative stress, through chronic exercise or antioxidants, can decrease the negative effects induced by excessive amounts of oxidative stress. Transient increases in oxidative stress produced during acute exercise facilitate beneficial vascular training adaptations, but the effects of non‐specific antioxidants on exercise training‐induced vascular adaptations remain elusive. Circulating angiogenic cells (CACs) are an exercise‐inducible subset of white blood cells that maintain vascular integrity. We investigated whether mitochondria‐specific antioxidant (MitoQ) supplementation would affect the response to 3 weeks of endurance exercise training in CACs, muscle mitochondrial capacity and maximal oxygen uptake in young healthy men. We show that endurance exercise training increases multiple CAC types, an adaptation that is not altered by MitoQ supplementation. Additionally, MitoQ does not affect skeletal muscle or whole‐body aerobic adaptations to exercise training. These results indicate that MitoQ supplementation neither enhances nor attenuates endurance training adaptations in young healthy men.